Production and characterization of pellets using Avicel CL611 as spheronization aid. (March 2014) - Puah, Sin Yee; Yap, Hsiu Ni; Chaw, Cheng Shu
Abstract Purpose: The study looked into the feasibility of producing pellet using Avicel CL611 as spheronization aid by the extrusion/spheronization technique. Methods: Pellets were formulated to contain either 20% or 40% Avicel CL611 and lactose monohydrate as the other sole ingredient. Water is used as liquid binder. Quality of pellets and extrudates were analyzed for size distribution, shape, surface tensile strength and disintegration profile. Results: More water was needed when higher Avicel CL611 fraction was used during the production of pellets. The pellets of larger size were obtained by increasing the water content. Pellets with aspect ratios of ∼1.1 were produced with high spheronization speed at short residence time. Higher tensile strength was achieved when increasing the water content and the fraction of Avicel CL611 during pellet production. These pellets also took longer time to disintegrate, nonetheless all the pellets disintegrated within 15 min. A positive linear relationship was obtained between the tensile strength and time for pellets to disintegrate. Conclusion: Strong but round pellets that disintegrate rapidly could be produced with Avicel CL611 as spheronization aid using moderately soluble compounds such as lactose.